KAJIAN KARAKTERISTIK LAHAN UNTUK MENDUKUNG PENYUSUNAN MODEL DECISION SUPPORT SYSTEM (DSS) OPTIMALISASI LAHAN DI KABUPATEN PANGKEP - Nurmiaty Nurmiaty; Samsu Arif; Andi Ridwan; Rahmad D; Yunarti Yunarti (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2023)
The biophysical characteristics and environmental conditions of the land are required for the development of a Decision Support System (DSS) model for land optimization. The purpose of this study was to examine the characteristics of land cover, and the biophysical and environmental conditions of the land in Pangkep Regency. Suboptimal land identification and analysis of land and climate characteristics are carried out on the basis of secondary data obtained from satellite images, both land cover data in 2022, data in the form of three-dimensional DEM (Digital Elevation Model), and land characteristic data in the form of land system maps produced by the Geospatial Information Agency. The land cover in the Pangkep Regency area consists of fourteen types of land cover dominated by jungles, rice fields, and ponds. Flat topography with slopes of 0-2% and geological formations of alluvium and coastal deposits, Tonasa Formation, and Sekala Formation are dominant in Pangkep Regency. The dominant soil characteristic in this region is a lithosol soil type, soil depth more than 150 cm, soil pH is slightly acidic (5.6-6.5), clay texture, soil drainage criteria are inhibited and good, soil salinity in the range of 0.33%, C-Organic content with very low and low criteria, medium soil CEC, low total N value with a range of 0.1–0.21% and medium with 0.22–0.51%, Soil potassium content including very low criteria (<10 mg/100g) is in the range of 0.05 – 0.2 mg/100g and dominant 0.2 mg/100g, and rock abundance is 100+. The rainfall in this region is predominantly 2500 mm.th-1 and the average temperature is 23 - 32°C.